PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN MELALUI FAKTOR BUDAYA DI KABUPATEN LAHAT - Andayani, Lestari (Universitas muhammadiyah palembang, 2018)
This study aims to determine and analyze the influence of products andpromotion of the decision to purchase instant noodles through culturalfactors as an intervening variable in Lahat District. The research design usedin this study is descriptive explanatory research with a quantitative approach.The analytical method used is quantitative and qualitative methods. Thevariables used are 2 independent variables namely Product and Promotionvariables and the dependent variable is the Purchase Decision plus theintervening variables namely Cultural Factors. Data samples used in thestudy were 367. The analytical tool used was the classical assumption modeltest, path analysis, and hypothesis testing.Based on the results of the studyfound that: (1) Products have a significant positive effect on cultural factors;(2) Promotion has a significant positive effect on cultural factors; (3)Products have a significant positive effect on Purchasing Decisions; (4)Promotion has a positive and insignificant effect on Purchase Decisions; (5)Cultural factors have a significant positive effect on Purchase Decisions; (6)There is a mediating influence on the cultural factor on the indirect influenceof the product on the purchase decision; and (7) There is a mediatinginfluence on Cultural Factors on the indirect influence of Promotion onPurchase Decisions